Perceptions of shariah scholars on shariah audit in Malaysian takaful industry - Mohamad Puad, Noor Aimi; Abdullah, Nurdianawati Irwani; Shafii, Zurina (International Research Centre of Islamic Economics and Finance (IRCIEF), International Islamic University College Selangor (KUIS), 2019)
Takaful is shariah compliant insurance scheme which become an important component in the Islamic financial system in Malaysia. Takaful industry in Malaysia is relatively young compared to other sectors in the financial industry, but it has enjoyed robust growth. However, despite the robust growth, Takaful industry also continues to face several challenges such as ineffective governance practices. Ineffective governance practice will lead to the possibility of facing shariah risk and incident of shariah risk in their activities and operation. Shariah audit function is one of the component of governance that play a role in ensuring the takaful operator to have a sound and effective internal control system of shariah compliance. This study aim to examine the shariah scholars’ perception on current shariah audit process and scope particularly in Takaful industry. Semi-structured interviews was conducted with shariah scholars who are members of the Shariah boards in various Takaful Operators. The finding discovers that there are different points of view demonstrated by the Shariah scholars. This study may provide relevant guidelines for future development of shariah audit practices in Islamic financial institutions in achieving maqasid shariah.